O venire contra factum proprium nas relações entre empresas regidas por contratos de adesão - Amaral, Maria Luisa Rodrigues (2022)
This study aims to analyze the legal validity of certain acts practiced by private legal entities that are involved in a contractual relationship governed by a subscription contract that has lost the balance between the rights and duties of the parties within, in order to re-establish the contractual equilibrium. The purpose of this analysis is to determine what is the best way to accommodate the interests of the parties involved in the contractual relationship without infringing general rules and contractual principles